Evaluation of the Implementation of Pedagogic Competence Training Policy: Analysis of the Effectiveness of the Teacher Human Resource Development Program : (Dili District, Timor-Leste) - Dulce Pereipra Lopes; Suparno Suparno; Aris Toening Winarni (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates the effectiveness of teacher training policy implementation in Dili Regency, Timor-Leste, utilizing the CIPP (Context, Input, Process, Product) evaluation model. A structured survey was administered to 150 teachers and education stakeholders to assess key determinants influencing implementation outcomes. Quantitative analysis employed Pearson correlation, multiple regression, and path analysis to examine relationships among variables. Findings revealed strong correlations between all independent variables and implementation effectiveness (r > 0.60, p < 0.01). The multiple regression model accounted for 76.3% of the variance in implementation effectiveness (R² = 0.763, F = 123.45, p < 0.001), with Policy Standards exerting the greatest influence (β = 0.243), followed by Resources (β = 0.203) and Implementer Disposition (β = 0.201). Path analysis confirmed the significance of all direct causal pathways, reinforcing the robustness of the model. These results underscore the critical role of clear policy standards, adequate resource allocation, and implementer commitment in enhancing the success of teacher training programs. The study contributes empirical evidence to the discourse on education reform in developing and post-conflict regions, highlighting strategic priorities for policy makers and practitioners. By aligning training initiatives with contextual realities and stakeholder capacities, the findings offer actionable insights for improving teacher professional development in Timor-Leste and similar settings.